DETERMINATION OF THE CRITICAL INDICATORS OF RAOD PERFORMANCE FOR DISASTER EVACUATION ROUTE IN THE COASTAL AREA, PADANG CITY, INDONESIA - Insannul Kamil; Difana Meilani; Nilda Tri Putri; Buang Alias; Mego Plamonia (International Conference on Coastal and Delta Areas, 2015)
It is the time for road infrastructure management system to switch the perspective of life plan-based management to another approach which is more efficient in terms of budgeting and can optimize road performance. The use of performance indicators has been recommended for this. This study aims to formulate the performance indicators for Performance Based Contracting (PBC) method widely used now now. These performance indicators are formulated for West Sumatera Province, designated as disaster zones. The integration of the three qualitative methods, namely the Delphi method, AHP and method of Natural Cut-off Point has succeeded in formulating indicators. Delphi method is used to identify indicators, while the AHP is used to prioritize the indicators and the last, the method of Natural Cut-off Point is used to select the critical indicators. A total of six critical indicators are identified, namely damage at the end of pavement, drainage, culverts, Potholes, width of pavement and cracking.Keywords: Indicators, road performance, critical, disaster and coastal area.